To investigate factors preventing the care-givers from accessing the social grants and other benefits entitled to the orphans and vulnerable children (OVC) under their care - Tshikongo, Aktofel Ndetshipanda (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)-- Stellenbosch University, 2013.